2014
DOI: 10.1007/s12663-014-0626-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Betamethasone and Sodium Hyaluronate Combination with Betamethasone Alone After Arthrocentesis in the Treatment of Internal Derangement of TMJ—Using Single Puncture Technique: A Preliminary Study

Abstract: Although patients benefitted from both techniques, arthrocentesis with intra-articular injection of betamethasone and sodium hyaluronate combination is superior to arthrocentesis with betamethasone injection alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
1
9
0
8
Order By: Relevance
“…It should be noted that, as demonstrated in several previous studies, the use of bite splint shows a high efficacy [36], as well as the use of intra-articular infiltrations of betamethasone, hyaluronic acid and platelet-rich plasma [28,29,[31][32][33][34][35]37,38]. However, most of the studies associate them with more invasive procedures, such as arthrocentesis that is very effective in the TMJDs and can be performed on an outpatient basis under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that, as demonstrated in several previous studies, the use of bite splint shows a high efficacy [36], as well as the use of intra-articular infiltrations of betamethasone, hyaluronic acid and platelet-rich plasma [28,29,[31][32][33][34][35]37,38]. However, most of the studies associate them with more invasive procedures, such as arthrocentesis that is very effective in the TMJDs and can be performed on an outpatient basis under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In the current literature, there are several studies that have compared the outcome of the use of hyaluronic acid and corticosteroids [16,[28][29][30][31][32], but very few have focused on the benefits of the use of platelet-rich plasma [33][34][35]. To the authors' knowledge, there is no research currently available that compares the use of these three products in TMJ arthralgia.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated combined therapy with corticosteroids in various pathologies, as knee osteoarthritis, stenosing tenosynovitis of fingers flexor tendons, internal derangement of temporomandibular joint, adhesive capsulitis and lateral epicondylitis (Tab. XII) 89,148,[153][154][155][156][157] . Despite the different indications and protocols, all these studies suggested the superiority of the therapeutic association in terms of efficacy (pain reduction) compared to the use of each treatment alone.…”
Section: Combination Therapy With Ha Association With Corticosteroidsmentioning
confidence: 99%
“…Multiple studies with different follow-up periods have shown that a single arthrocentesis procedure results in a decrease in pain ranging from 37 to 86%. 3,31,36,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] These studies generally involve heterogeneous populations and most inject HA or CS as part of the procedure. These studies are not double blinded and most are not randomized, which introduces potential bias and confounders.…”
Section: Discussionmentioning
confidence: 99%
“…They are used in multiple joints for inflammatory arthropathy, including the TMJ. 32,[42][43][44][45] When comparing HA with CS, some investigators have found them equally effective, 42,45 whereas others have found HA to be superior. 32 The relative lack of evidence supporting or refuting the use of HA or CS makes recommending either problematic.…”
mentioning
confidence: 99%